Conjuncted fertılızatıon regımes boost seed yıeld and chemıcal composıtıon of sunflower (Helianthus annuus L.) - Eliçin, Ahmet Konuralp; Öztürk, Ferhat; Koca, Yakup Kenan; Kızılgeçi, Ferhat; Asan, Nihan Tazebay (PARLAR SCIENTIFIC PUBLICATIONS, 2022)
In the frame of sustainable farming systems to decrease chemical fertilizers use and protect the environment , organic fertilization regimes hold potential as an alternative strategy to supply essential nutrients to crops. A field trial was conducted to sort out the most superior fertilization regime for boosting sunflower production and quality under semi-arid conditions. Treatments included chemical fertilizer (Cf) (80 kg N ha(-1) and 80 kg P205 ha(-1)), manure from sheep barn manure (MSB) (5161 kg ha(-1)), manure from cattle barn (MCB) (4878 kg ha(-1)), liquid manure from cattle barn (LMCB) (27580 kg ha(-1)) and vermicompost (VCm) (4000 kg ha(-1)), while a control treatment was kept for comparison purpose. The randomized complete block design (RCBD) with regular arrangement was implied to execute the experiment having three replications. The results exhibited that MSB outperformed rest of fertilization regimes for plant height and leaf number. In contrast, the maximum 1000 seed weight and seed yield were recorded by LMCB. The MCB remained unmatched for protein content, while no significant effect of fertilization regimes was recorded for oil content. Regarding chemical composition, control exhibited the maximum palmitic and stearic acids, while MSB gave the highest arachidic acid.
Keywords: SPAD; Fatty acid; Protein content; CM1000 chlorophyll meter